PEMANFAATAN BANTUAN LUAR NEGERI DALAM PENINGKATAN EKONOMI KERAKYATAN TANI KAKAO DI PROVINSI SULAWESI BARAT (Studi Program Swisscontact Periode 2013-2018) - Wandi Abbas; Abid Muhtarom (JPIM (Jurnal Penelitian Ilmu Manajemen), 2018)
Swisscontact is a private and independent Swiss foundation that promotes sustainable economic growth in developing countries. Founded in 1959, Swisscontact works exclusively in international cooperation and development and implements their own projects as well as trustees. The Swisscontact headquarters are in Zurich and have a close relationship with the private sector from the start. Swisscontact has prinspi that treats all people served and all partners with respect. In addition, Swisscontact also respects the workplace environment and complies with the rules of conduct well. (Swisscontact.org; 2017) One of the problems considered important in analyzing a phenomenon in international relations is the level of analysis. Bruce Russett and Harvey Starr offer six levels of analysis: individuals (individuals), individuals (in decision-making roles), government structures, communities, decision-making networks and world systems. This research will use community analysis unit because this unit of analysis is the most competent in this research with qualitative method. The implementation of the Swisscontact training program also encountered several obstacles such as; farmers, timetable arrangement of other farmers activities with the implementation of the same field school. While from Swisscontact, access to training loops is very difficult, the weather in the working area is changing so that the provision of training materials is less than the maximum. The influence of development and increase of export of Indonesian cocoa products especially West Sulawesi in recent years has increased significantly especially in the year 20142018. One of them is because the implementation of Swisscontact program in some regions of Indonesia province has given maximum result so that it has an effect to increase the production and export of Indonesian cocoa beans overseas.